Pengembangan Kreativitas dan Keterampilan Praktikal Siswa MI Muhammadiyah Lubuk Banjar Melalui Pemanfaatan Limbah Barang Bekas - Mardalena, Ervin; Kenamon, Mardiah; Kontesa, Melia; Afrilia, Anita; Putri, Felicia Helena; Wati, Sri Rica (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to develop the creativity and practical skills of students at MI Muhammadiyah Lubuk Banjar through the use of recycled materials as learning media. The recycled materials used include cardboard, plastic bottles, beads, and sticks, which are processed into various crafts through hands-on activities. This study uses a qualitative descriptive method with MI Muhammadiyah Lubuk Banjar students as the research subjects. Data collection techniques were carried out through observation, practical activities, and documentation of the learning process and student work. The results show that the use of used items as learning media can increase student creativity, develop practical skills, especially fine motor skills, accuracy, and neatness, as well as foster an attitude of caring for the environment. In addition, this practice-based learning activity encourages students to be more active, innovative, confident, and able to work together in groups. Thus, the use of used items can be used as an alternative learning medium that is effective, educational, contextual, and environmentally friendly in learning at Madrasah Ibtidaiyah.